Catalogue-based guideline for misuse case - Khairuddin, Muhammad Asyraf; Abd Ghani, Abdul Azim; Zulzalil, Hazura; Hassan, Saadah (Little Lion Scientific, 2022)
Misuse case is one of the security requirement elicitation techniques that are easy to use and learn. Unfortunately, the current guideline provided is too general. The process of identifying the misuse case and threats is open for the analyst's interpretation. Lack of knowledge in security threats also can make it worse. These problems can lead to analysis paralysis situation. In this paper, we proposed a catalogue-based guideline to support misuse case techniques to elicit security requirements. This guideline consists of two catalogues used to assist software developers in identifying attacks and threats from a misuse case diagram. We experimented with selected students to evaluate the effectiveness of the guideline in identifying threats and types of threats. We also evaluated the usability of the guideline by conducting experts reviews. Experiment's result shows sufficient evidence that using the misuse case with the proposed catalogue-based guideline is more effective in identifying threats and types of threats than using the misuse case without a guideline. Expert review's result also shows that the catalogue-based guideline is more usable in identifying threats than without using the guideline.